2017
DOI: 10.1017/s0031182017002086
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological investigation of a severe rumen fluke outbreak on an Irish dairy farm

Abstract: Although the rumen fluke, Calicophoron daubneyi is now very common and widespread throughout Western Europe, reports of clinical cases are still rare. This study explores the epidemiological background to a severe rumen fluke outbreak in 6-month-old heifers on a dairy farm in Ireland. Sequence analysis of the cytochrome oxidase subunit 1 (Cox1) gene of the rumen fluke metacercariae on pasture failed to identify predominant, possibly pathogenic subtypes. However, estimates of metacercarial load indicated that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
0
21
0
2
Order By: Relevance
“…It has also been suggested that C. daubneyi is adapting to out-compete the already endemic F. hepatica in their shared environment and snail intermediate host species ( 7 ). Furthermore, the widespread use of fasciolicides, to target liver fluke—most but not all are specific for liver fluke—may be giving C. daubneyi further competitive advantage over F. hepatica , such that C. daubneyi may eventually replace F. hepatica as the most prevalent endemic trematode in the UK/Ireland ( 8 ).…”
Section: Paramphistomosis—an Established Infection In European Livestmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been suggested that C. daubneyi is adapting to out-compete the already endemic F. hepatica in their shared environment and snail intermediate host species ( 7 ). Furthermore, the widespread use of fasciolicides, to target liver fluke—most but not all are specific for liver fluke—may be giving C. daubneyi further competitive advantage over F. hepatica , such that C. daubneyi may eventually replace F. hepatica as the most prevalent endemic trematode in the UK/Ireland ( 8 ).…”
Section: Paramphistomosis—an Established Infection In European Livestmentioning
confidence: 99%
“…Whilst paramphistomes are common in the UK/Ireland, clinical disease (i.e., poor condition/emaciation, with or without death, associated with acute infection) as described by Millar et al ( 12 ) and Mason et al ( 15 ) is still relatively rare. However, fatal disease outbreaks, linked to significant immature parasite burdens, are on the rise in both sheep and cattle ( 8 , 11 , 12 , 15 ). For example, in a particularly severe outbreak on an Irish farm, 6-months old dairy heifers ingested an estimated 5,334 metacercariae each day over 3 weeks ( 8 ).…”
Section: Daubneyi —A Growing Threat To Uk Agriculture?mentioning
confidence: 99%
See 1 more Smart Citation
“…Intestinale Paramphistomidose führt bei Massenbefall zu ernsthaften Erkrankungen, wobei keine spezifische Symptomatik vorliegt [5][8] [44]. Vorberichtlicher Weidegang auf stark vernässten Böden ist für akute Ausbrüche pathognomonisch [47]. Obwohl die jährliche Inzidenz für intestinale Paramphistomidose bisher unter 5 % liegt [72], sollte bei Weidetieren mit akutem Durchfallgeschehen differenzialdiagnostisch auch an den Nachweis von Jungegeln im Kot gedacht werden [9] [12].…”
Section: Diskussionunclassified
“…Acute, clinical paramphistomosis is caused when grazing stock ingest large numbers of metacercariae from pasture, which then excyst en masse in the duodenum (4). The newly excysted juvenile (NEJ) flukes then migrate into the intestinal submucosa causing significant damage to the host tissue (5).…”
Section: Introductionmentioning
confidence: 99%